Orissa, her monuments and their tales - Pani, Subas (Vidyapuri, 1987)
Elephant rock edict, Dhauli -- Lingaraj Temple, Bhubaneswar -- Jagannath Temple, Puri-I -- Jagannath Temple-II -- Barabati -- Kalijai Temple -- Remuna Temple -- Sakhigopal Temple -- Sun Temple.